Induced Membrane Technique Is Effective for the Management of Acute Traumatic Bone Loss in Both Diaphyseal and Metaphyseal Lower Extremity Fractures. Issue 5 (May 2023) - Steffenson, Lillia; Roszman, Alex; Wallace, Cameron; Kot, Taylor Corbin; Wallace, Stephen; Spitler, Clay; Bergin, Patrick; Githens, Michael; Haller, Justin
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objective: To compare outcomes of Masquelet-induced membrane technique (IMT) in metaphyseal and diaphyseal fractures with acute bone loss. Design: Retrospective cohort study. Setting: Four Level 1 Academic Trauma Centers. Patients/Participants: Patients acutely treated with IMT for traumatic lower extremity bone loss at 4 Level 1 trauma centers between 2010 and 2020. Intervention: Operative treatment with placement of cement spacer within 3 weeks of initial injury followed by staged removal and bone grafting to the defect. Main Outcome Measurements: Fracture union, infection, revision grafting, time to union, and amputation. Results: One hundred twenty fractures met inclusion criteria, including 43 diaphyseal fractures (DIM) and 77 metaphyseal fractures (MIM). Demographic characteristics were not significantly different, except for age (DIM 34 years vs. MIM 43 years, P < 0.001). Union after treatment with IMT was 89.2% overall. After controlling for age, this was not significantly different between DIM (41/43, 95.3%) and MIM (66/77, 85.7%) ( P = 0.13) nor was the rate of infection between groups. There was no difference in any secondary outcomes. Conclusions: The overall union rate in the current series of acute lower extremity fractures treated with the induced membrane technique was 89%. There was no difference in successful union between patients with diaphyseal bone loss or metaphyseal bone loss treated with IMT. Similarly, there was no difference in patients with tibial or femoral bone loss treated with induced membrane. Defect size after debridement may be more prognostic for secondary operations rather than the limb segment involved or the degree of soft-tissue injury. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.